2020
DOI: 10.3390/foods10010020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Cronobacter sakazakii Strains Isolated from Powdered Milk

Abstract: Cronobacter spp. are opportunistic pathogens of the Enterobacteriaceae family. The organism causes infections in all age groups, but the most serious cases occur in outbreaks related to neonates with meningitis and necrotizing enterocolitis. The objective was to determine the in silico and in vitro putative virulence factors of six Cronobacter sakazakii strains isolated from powdered milk (PM) in the Czech Republic. Strains were identified by MALDI-TOF MS and whole-genome sequencing (WGS). Virulence and resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 83 publications
1
20
2
Order By: Relevance
“…These values are similar to those reported by Holý et al (2019) , where 100% and 66.7% of the C. sakazakii clinical strains evaluated adhered to and invaded the N1E-115 cell line, respectively. Recently, Holý et al (2021) , when evaluating clinical strains of C. sakazakii with the N1E-115 cell line, found a value of 2.2 × 10 6 CFU/mL for adherence, which is much lower than those found in our study. However, the rates of invasion of C. sakazakii in our study are lower than those reported by various authors, such as Mange et al (2006) ; Townsend et al (2007) , Parra-Flores et al (2018a) , and Holý et al (2019) .…”
Section: Resultscontrasting
confidence: 92%
See 2 more Smart Citations
“…These values are similar to those reported by Holý et al (2019) , where 100% and 66.7% of the C. sakazakii clinical strains evaluated adhered to and invaded the N1E-115 cell line, respectively. Recently, Holý et al (2021) , when evaluating clinical strains of C. sakazakii with the N1E-115 cell line, found a value of 2.2 × 10 6 CFU/mL for adherence, which is much lower than those found in our study. However, the rates of invasion of C. sakazakii in our study are lower than those reported by various authors, such as Mange et al (2006) ; Townsend et al (2007) , Parra-Flores et al (2018a) , and Holý et al (2019) .…”
Section: Resultscontrasting
confidence: 92%
“…The cgMLST scheme analysis revealed a cluster of six C. sakazakii ST1 strains with one to three allele differences and ST83 strain with 3,043 allele difference ( Figure 1 ). C. sakazakii ST1 has been most frequently isolated from commercial PIF in various countries, from processing equipment for PIF manufacturing, and from patients with fatal meningitis, septicemia, or urinary tract infections ( Joseph and Forsythe, 2012 ; Fei et al, 2015 ; Holý et al, 2021 ; Parra-Flores et al, 2021 ). Lepuschitz et al (2017) , in their multicenter study of infections caused by C. sakazakii in Europe, studied eight isolates identified as C. sakazakii ST1 that included two isolates from newborns’ feces with an epidemiological link to an outbreak in Austria in 2009.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, 14% of C. sakazakii isolates were high-level colistin-resistant, which is in good agreement with some former surveys (27,28). Microbial cells within bio lms have been exhibited to be 10-1000 times more resistant to antibiotics than the planktonic cells (29).…”
Section: Discussionsupporting
confidence: 90%
“…The species were characterized using multilocus sequence typing (MLST) ( 13 ) extracted from the PubMLST Cronobacter database ( https://pubmlst.org/organisms/cronobacter-spp ) and core genome MLST (cgMLST) using SeqSphere+ v6.0. with default settings as previously described ( 7 , 14 ). All isolates had >97% good cgMLST targets, sequence type 1 (ST1) and ST83, and clonal complex 1 (CC1) and CC83.…”
Section: Announcementmentioning
confidence: 99%